2023
DOI: 10.1037/xlm0001174
|View full text |Cite
|
Sign up to set email alerts
|

Why do judgments of learning modify memory? Evidence from identical pairs and relatedness judgments.

Abstract: Research has observed that monitoring one’s own learning modifies memory for some materials but not for others. Specifically, making judgments of learning (JOLs) while learning word pairs improves subsequent cued-recall memory performance for related word pairs but not for unrelated word pairs. Theories that have attempted to explain this pattern of results assume that people attend to and process cue-target relatedness during learning more when making JOLs than they spontaneously do when not making JOLs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Importantly, small-scale meta-analyses across our experiments revealed that this finding is not due to insufficient statistical power: CCMAs revealed no overall effect of JOL reactivity and a small effect of positive reactivity for easy materials, but not for more difficult materials. While the latter finding is consistent with previous basic research showing positive reactivity for relatively easy materials (e.g., Halamish & Undorf, 2022;Janes, Rivers, et al, 2018;Soderstrom et al, 2015;Witherby & Tauber, 2017), a small effect that is confined to easy materials probably is of little relevance for educational settings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, small-scale meta-analyses across our experiments revealed that this finding is not due to insufficient statistical power: CCMAs revealed no overall effect of JOL reactivity and a small effect of positive reactivity for easy materials, but not for more difficult materials. While the latter finding is consistent with previous basic research showing positive reactivity for relatively easy materials (e.g., Halamish & Undorf, 2022;Janes, Rivers, et al, 2018;Soderstrom et al, 2015;Witherby & Tauber, 2017), a small effect that is confined to easy materials probably is of little relevance for educational settings.…”
Section: Discussionsupporting
confidence: 91%
“…There now is much evidence that the mere act of making immediate JOLs impacts memory performance (Double & Birney, 2019). An increasing number of studies show that making JOLs enhances recall performance for related word pairs compared to studying for a comparable duration ( positive reactivity ; Halamish & Undorf, 2022; Janes, Rivers, et al, 2018; Myers et al, 2020; Soderstrom et al, 2015; Tauber & Witherby, 2019; Witherby & Tauber, 2017), whereas making JOLs for unrelated word pairs has either no effect (e.g., Soderstrom et al, 2015) or impairs recall ( negative reactivity ; Janes, Rivers, et al, 2018; Mitchum et al, 2016). Furthermore, making JOLs enhanced free-recall and recognition performance for single words (Myers et al, 2020; Senkova & Otani, 2021) and long-term learning of related pairs (Witherby & Tauber, 2017).…”
Section: Reactivity Of Immediate Jolsmentioning
confidence: 99%
“…One consideration is the potential reactivity of collecting metacognitive judgments on the basic cognitive processes involved in performing the main task at hand. For instance, in memory research, there are consistent findings that collecting judgments of learning improves success in remembering related word pairs (e.g., Sky—Kite) but not unrelated ones (e.g., Sky—Vase; see Halamish and Undorf 2023 for a review). In reasoning and problem solving, in contrast, the results have been less consistent (e.g., Double and Birney 2017 ; Thompson et al 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…Subjective or metacognitive monitoring during learning is of particular interest because these processes can enhance learning effectiveness by guiding the allocation of resources at a time when information remains available for learning. As a typical example of metacognitive monitoring, judgments of Learning (JOLs) are individuals' assessments of the likelihood that currently learned items will be successfully retrieved on subsequent tests, usually occurring after learning and before testing 1 , 2 . A common occurrence in judgments of Learning (JOLs) is that individuals tend to overestimate their ability to recall information learned during the learning phase, yet fail to recall it during a subsequent memory test.…”
Section: Introductionmentioning
confidence: 99%